Metabolomics and genetics of reproductive bud development in Ficus carica var. sativa (edible fig) and in Ficus carica var. caprificus (caprifig): similarities and differences - Marcotuli, Ilaria; Mandrone, Manuela; Chiocchio, Ilaria; Poli, Ferruccio; Gadaleta, Agata; Ferrara, Giuseppe (Frontiers in Plant Science, 2023)
In fig, reproductive biology comprises cultivars requiring or not pollination, with female trees (edible fig) and male trees (caprifig) bearing different types of crops. Metabolomic and genetic studies may clarify bud differentiation mechanisms behind the different crops. Buds of two fig cultivars, ‘Petrelli’ (San Pedro type) and ‘Dottato’ (Common type), and one caprifig, were deep analyzed by using a targeted metabolomic analysis and genetic investigation through RNA sequences and candidate genes investigation. In this work, proton nuclear magnetic resonance (1H NMR-based metabolomics) has been used to analyze and compare buds of the caprifig and the two fig cultivars collected at different times of the season. Metabolomic data of buds collected on caprifig, ‘Petrelli’ and ‘Dottato’ were treated individually, building three separate Orthogonal Partial Least Squared (OPLS) models, using as ‘y’ variable the sampling time that allowed to identify correlations among metabolomic profiles of buds. The sampling times revealed different patterns between caprifig and the two edible fig cultivars. A significant amount of glucose and fructose was found in ‘Petrelli’, differently from ‘Dottato’, in the buds in June suggesting that these sugars are not only used by the ripening brebas of ‘Petrelli’ but are also directed towards the developing buds on the current year shoot for either a main crop (current season) or brebas (successive season). Genetic characterization through the RNA seq of buds and comparison with literature allowed the identification of 473 down-regulated genes, with 22 only in profichi, and 391 up-regulated genes with 21 only in mammoni.